2008
DOI: 10.5424/sjar/2008061-295
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of three metaldehyde pellets marketed in Argentina, on the control of Deroceras reticulatum (Müller) (Pulmonata: Stylommatophora)

Abstract: Management of the grey slug, Deroceras reticulatum (Müller) (Pulmonata: Stylommatophora), in Argentina, has been limited to the use of pelleted toxic baits containing metaldehyde. The most important molluscicides in the Argentinean market are Clartex (Rizobacter Argentina S.A.), Acay (Acay Agro S.R.L.) and Babotox (Huagro S.A.). The aim of this work was to investigate the efficacy and dose of those commercial baits against D. reticulatum. The molluscicides (Acay, Clartex and Babotox), at doses of 3, 4 and 5 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
14
1
3
Order By: Relevance
“…The adoption of NT system in southeastern Buenos Aires Province increased some groups of organisms like slugs and pill bugs in some fields, which became pests in crops (Faberi et al, 2006;Clemente et al, 2008;Salvio et al, 2008;Faberi et al, 2009). In recent works Diovisalvi et al (2008) and Domínguez et al (2009) determined that there are slightly changes in some properties of the soil related to the soils sustainability between CT and NT.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of NT system in southeastern Buenos Aires Province increased some groups of organisms like slugs and pill bugs in some fields, which became pests in crops (Faberi et al, 2006;Clemente et al, 2008;Salvio et al, 2008;Faberi et al, 2009). In recent works Diovisalvi et al (2008) and Domínguez et al (2009) determined that there are slightly changes in some properties of the soil related to the soils sustainability between CT and NT.…”
Section: Discussionmentioning
confidence: 99%
“…Damages are similar to the common no tillage pest, slugs. Glen & Moens (2002), Moens & Glen (2002), Faberi et al (2006 and Salvio et al (2008) observed that slug damage to plants is caused at sowing and immediately after germination. Similar damages occur with A. vulgare, it feeds on seeds and seedlings, causing a reduction in plant density.…”
Section: Introductionmentioning
confidence: 99%
“…Such protective behaviors can prevent free imbibition of molluscicidal compounds into the inner body cavities. On the other hand, molluscicidal baits act as stomach poisons [ 49 ]. Hence damage to the gastric epithelium is the main mechanism of action [ 14 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%